Metal artifact reduction for flat panel detector intravenous CT angiography in patients with intracranial metallic implants after endovascular and surgical treatment. (7th September 2015) - Pjontek, Rastislav; Önenköprülü, Belgin; Scholz, Bernhard; Kyriakou, Yiannis; Schubert, Gerrit A; Nikoubashman, Omid; Othman, Ahmed; Wiesmann, Martin; Brockmann, Marc A
Abstract : Background: Flat panel detector CT angiography with intravenous contrast agent injection (IV CTA) allows high-resolution imaging of cerebrovascular structures. Artifacts caused by metallic implants like platinum coils or clips lead to degradation of image quality and are a significant problem. Objective: To evaluate the influence of a prototype metal artifact reduction (MAR) algorithm on image quality in patients with intracranial metallic implants. Methods: Flat panel detector CT after intravenous application of 80 mL contrast agent was performed with an angiography system (Artis zee; Siemens, Forchheim, Germany) using a 20 s rotation protocol (200° rotation angle, 20 s acquisition time, 496 projections). The data before and after MAR of 26 patients with a total of 34 implants (coils, clips, stents) were independently evaluated by two blinded neuroradiologists. Results: MAR improved the assessability of the brain parenchyma and small vessels (diameter <1 mm) in the neighborhood of metallic implants and at a distance of 6 cm (p<0.001 each, Wilcoxon test). Furthermore, MAR significantly improved the assessability of parent vessel patency and potential aneurysm remnants (p<0.005 each, McNemar test). MAR, however, did not improve assessability of stented vessels. Conclusions: When an intravenous contrast protocol is used, MAR significantly ameliorates the assessability of brain parenchyma, vessels, and treated aneurysms in patients with intracranial coils or clips.